2021
DOI: 10.1073/pnas.2024562118
|View full text |Cite
|
Sign up to set email alerts
|

MK2 degradation as a sensor of signal intensity that controls stress-induced cell fate

Abstract: Cell survival in response to stress is determined by the coordination of various signaling pathways. The kinase p38α is activated by many stresses, but the intensity and duration of the signal depends on the stimuli. How different p38α-activation dynamics may impact cell life/death decisions is unclear. Here, we show that the p38α-signaling output in response to stress is modulated by the expression levels of the downstream kinase MK2. We demonstrate that p38α forms a complex with MK2 in nonstimulated mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…We performed TSA in intact cells to test whether NC-p38i compounds could bind to the endogenous p38α protein, which is normally forming complexes with other proteins such as MK2 36 . Cells were treated with compounds NC-37 or NC-38 or with the vehicle DMSO, and then heated in a temperature range between 39 °C and 52 °C to monitor protein unfolding and aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…We performed TSA in intact cells to test whether NC-p38i compounds could bind to the endogenous p38α protein, which is normally forming complexes with other proteins such as MK2 36 . Cells were treated with compounds NC-37 or NC-38 or with the vehicle DMSO, and then heated in a temperature range between 39 °C and 52 °C to monitor protein unfolding and aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work established a key role of the nervous system in regulating stress responses in other tissues including the UPR in intestine 71 . More recent studies have illuminated that MAPK-dependent regulation of hyaluronidase (TMEM2) promotes ER homeostasis 72 and degradation of the p38 target MK2 functions as a feedback signal critical for stress-induced cell fate 73 as well as emerging evidence that p38 signaling has a crucial role in synaptic plasticity and neurodegenerative processes 74 . Our previous findings revealed that PMK-1 coordinates growth rate with stress responsiveness during larval development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Srk1 and MK2, although they have differences, they share functional characteristics. They regulate the cell cycle through Cdc25, form a complex with MAPK p38, and are degraded to terminate or modulate the stress response [28][29][30] . Our preliminary data also suggest a conservation of the negative feedback regulation of p38 by MK2 in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%